2023
DOI: 10.12928/spekta.v4i1.7613
|View full text |Cite
|
Sign up to set email alerts
|

Empowering Tourism Awareness Group Based on Sapta Pesona Concept to Actualize Agro-Tourism Villages in West Bangka

Maulana Arif,
Haiyudi Haiyudi,
Teng Teu

Abstract: Background: To be financially independent village seems to be a must to support the local economic freedom. Tourism becomes one among some promising sectors. However, the low level of local understanding towards the concept of agro-tourism is much needed to support the local government development, especially in Tebing Village, West Bangka. Contribution: The purpose of this program is to support the actualization of an agro-tourism village based on green rice fields through the formation of a tourism awareness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…A presentation named Sapta Pesona, which had seven principles that should be prioritized expressly for tourism, was given to improve public knowledge of tourism's idea, role, and function (Arif et al, 2023). Sapta Pesona's goal, created in 2012, is to support and advance the Indonesian tourist sector.…”
Section: Methodsmentioning
confidence: 99%
“…A presentation named Sapta Pesona, which had seven principles that should be prioritized expressly for tourism, was given to improve public knowledge of tourism's idea, role, and function (Arif et al, 2023). Sapta Pesona's goal, created in 2012, is to support and advance the Indonesian tourist sector.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have shown that factors such as economic, socio-cultural, environmental, interaction, awareness, and local development contribute to the perception of rural tourism by local people and farmers (Yilmaz and Merkez 2022). To support local economic freedom and development, it is necessary to increase local understanding of concepts such as agro-tourism (Arif, Haiyudi, and Teu 2023). Government policies should focus on building tourism-conscious areas based on local wisdom and fostering local and creative industries to create awareness and entrepreneurial characteristics among the local population (Andriansyah et al 2022).…”
Section: Literature Review 11 the Concept Of Awareness And Perception...mentioning
confidence: 99%